Organocatalyzed α-aminooxylation/amination of aldehydes and their sequential reactions: a versatile tool for the synthesis of bioactive molecules - Ahuja, Brij Bhushan; Sudalai, Arumugum (Bioactive Natural Products, 2020)
<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">This chapter introduces the sequential reactions of proline catalyzed α-aminooxylation and α-amination of aldehydes and its broad applications in the synthesis of bioactive molecules. It starts by presenting an overview of organocatalysis, particularly proline and its catalytic behavior. It then explains the proline catalyzed α-aminooxylation reaction and its sequential reactions one by one along with its applications in the synthesis of natural products. Next, it describes the <span class="small-caps" style="font-variant: small-caps; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-weight: 400;">l<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">- and <span class="small-caps" style="font-variant: small-caps; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-weight: 400;">d<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">-proline catalyzed α-amination and its sequential reactions. A full description of the synthetic scheme of natural products is provided.